Financial development, reallocation and growth: Firm heterogeneity matters. (1st November 2020) - Bas, Maria; Berthou, Antoine
Abstract: This paper investigates the heterogeneous effect of financial development on firm‐level growth. Our analysis relies on the experience of the rapid expansion of credit in Indian states, following the process of banking reforms in the early 1990s. Based on a survey of Indian manufacturing firms (1997–2006), we examine how changes in the access to finance by firms across Indian states affected the growth of firms located in the same location. Estimation results show that initially larger, more productive or more profitable firms benefit the most from the rapid expansion of credit across Indian states. These results are robust to various specifications that allow to control for other reforms taking place simultaneously, or for potential reverse causality. The aggregate impact of this heterogeneous effect is important: the main channel that explains sector‐level total factor productivity growth due to financial development is the reallocation of market shares across firms.